Behaviour change to address climate change. (December 2021) - Whitmarsh, Lorraine; Poortinga, Wouter; Capstick, Stuart
Abstract: Addressing climate change requires profound behaviour change, not only in consumer action, but also in action as members of communities and organisations, and as citizens who can influence policies. However, while many behavioural models exist to explain and predict mitigation and adaptation behaviours, we argue that their utility in establishing meaningful change is limited due to their being too reductive, individualistic, linear, deliberative and blind to environmental impact. This has led to a focus on suboptimal intervention strategies, particularly informational approaches. Addressing the climate crisis requires a focus on high-impact behaviours and high-emitting groups; interdisciplinary interventions that address the multiple drivers, barriers and contexts of behaviour; and timing to ensure interventions are targeted to moments of change when habits are weaker.